2006
DOI: 10.1111/j.1447-0756.2006.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

LycoRed as an alternative to hormone replacement therapy in lowering serum lipids and oxidative stress markers: A randomized controlled clinical trial

Abstract: Both HRT and LycoRed had a favorable effect on serum lipids and oxidative stress markers which were comparable. LycoRed can be used as an alternative to HRT to reduce the risk of atherosclerosis in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 31 publications
(60 reference statements)
0
24
0
2
Order By: Relevance
“…Epidemiological studies have shown that the consumption of lycopene-rich foods is inversely associated with the risk of diseases such as atherosclerosis (Misra et al, 2006), cardiovascular disease (Ito et al, 2006), prostate cancer (Zhang et al, 2007) and cognitive impairment (Akbaraly, Faure, Gourlet, Favier, & Berr, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have shown that the consumption of lycopene-rich foods is inversely associated with the risk of diseases such as atherosclerosis (Misra et al, 2006), cardiovascular disease (Ito et al, 2006), prostate cancer (Zhang et al, 2007) and cognitive impairment (Akbaraly, Faure, Gourlet, Favier, & Berr, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation with tomato extract capsules (4 mg lycopene) daily for 6 months decreased total cholesterol and LDL cholesterol levels in postmenopausal women [62]. Moreover, a reduction in LDL cholesterol to 17% by tomato juice has been reported [63].…”
Section: Human Studiesmentioning
confidence: 99%
“…The ER gained its normal pattern with restoration of ribosomes. The nucleus, mitochondria get its normality [25,26]. These results run barrel with Srinivasan [21], who showed that pretreatment with Lycopene offers protection to normal lymphocytes against γ-radiation-induced cellular damage due to free radical released by radiation reaction inside the cell.…”
Section: Discussionmentioning
confidence: 86%